1979
DOI: 10.1042/bj1820149
|View full text |Cite
|
Sign up to set email alerts
|

Limited-turnover studies on proton translocation in reconstituted cytochrome c oxidase-containing vesicles

Abstract: We have investigated ferrocytochrome c-induced proton ejection from reconstituted cytochrome c oxidase-containing vesicles using careful control of the number of enzyme turnovers. Ferrocytochrome c caused the appearance of protons at the vesicle exterior, and this could be abolished by using a protonophore. In addition, its decay was dependent on the permeability of the vesicle membranes to protons and the number of turnovers of the oxidase. These observations indicate that the ejection of protons was the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
68
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(76 citation statements)
references
References 27 publications
(14 reference statements)
8
68
0
Order By: Relevance
“…The fast proton efflux was fully abolished by proton ionophores or by omitting valinomycin from the medium (Krab & Wikstrom, 1978). Casey, Chappell & Azzi (1979) confirmed these results with cytochrome oxidase vesicles. Furthermore, by careful titration with the proton ionophore FCCP they showed that proton ejection was indeed the result of proton translocation and reported a (H+/e~) ratio of 0-9.…”
Section: (Iii) Planar Bilayerssupporting
confidence: 77%
“…The fast proton efflux was fully abolished by proton ionophores or by omitting valinomycin from the medium (Krab & Wikstrom, 1978). Casey, Chappell & Azzi (1979) confirmed these results with cytochrome oxidase vesicles. Furthermore, by careful titration with the proton ionophore FCCP they showed that proton ejection was indeed the result of proton translocation and reported a (H+/e~) ratio of 0-9.…”
Section: (Iii) Planar Bilayerssupporting
confidence: 77%
“…Ferrocytochrome c, prepared as in [30], was measured using a A~5 5 0 (reduced-oxidized) = 21 mM-' cm-' [34]. Ferrocytochrome c was oxidized by adding a few grains of ferricyanide.…”
Section: Cytochrome Assaymentioning
confidence: 99%
“…Reconstitution of the cytochrome oxidase vesicles was performed by the cholate dialysis method as described in [30]. The percentage of total cytochrome oxidase incorporated 'right-side out' was calculated as in [31] or after reduction by impermeant and permeant reducing agents in anaerobiosis in the absence of cyanide.…”
Section: Preparation Of Cytochrome C Oxidase and Cytochrome Oxidase Vmentioning
confidence: 99%
“…Oxygen uptake assays used conditions similar to [20]; uncoupling for respiratory control measurements was as in [7]. Proton translocation was at 3°C using phenol red [6] as modified by [7] except that the reduced cytochrome c was chromatographed and stored in 50 mM K$SOJl mM MOPS (pH 7.2). Protein determination was as in [21], compensating for phospholipid interference.…”
Section: Vesicular Oxidasementioning
confidence: 99%